First report of two deep-sea shrimps of the genus Acanthephyra A. Milne-Edwards, 1881 (Crustacea: Decapoda: Acanthephyridae) from southwestern Atlantic - Alves-Júnior, Flavio De Almeida; de Araújo, Marina De Sá Leitão Câmara; Bertrand, Arnaud; Souza-Filho, Jesser F. (Zootaxa, 2016)
This paper reports two deep-sea shrimps, Acanthephyra acanthitelsonis and A. armata from southwestern Atlantic waters. The samples were collected in two different moments, the first in the Potiguar Basin, northeast of Brazil (03/05° S; 38/35° W), covering the states of Rio Grande do Norte (RN) and Ceará (CE) in the year of 2011, and afterward on Rocas Atoll, located in the state of Rio Grande do Norte (RN) (3° 51’ S, 033° 49’ W; 3° 52’ S, 033° 47’ W) in the year of 2015. The occurrence of A. acanthitelsonis on Rocas Atoll and A. armata found along the continental slope in the Potiguar Basin, comprising both species, which were recorded for the first time in the southwestern Atlantic. This paper increases the number of Acanthephyra species recorded in Brazilian waters up to six and adds to our knowledge and distribution of deep-sea fauna in the south Atlantic.